(untitled) (Revista de Ciências Agroveterinárias, 2015)
Periodontal disease results from host inflammatory response to the accumulation of plaque, triggering the formation of dental calculus and gingivitis. The objective of this study was to evaluate the incidence of dental calculus (DC) and periodontal disease (PD) by dental group, dental arch and age of animals, using specifi c score tables for DC and PD. Twenty-five Beagle dogs were anesthetized and submitted to clinical examination of the oral cavity in order to measure the degree of DC and PD. There was a directly proportional increase between the DC, PD scores and the age of the animals. The upper jaw dental groups were most affected by DC and PD, when compared to the lower jaw. The incisors and canines stood out as the groups of teeth less and more affected by DC and PD, respectively.